(untitled) (Journal of Economics and Management Research, 2023)
تهدف هذه الدراسة إلى التعرف على أثر الشمول المالي في النمو الاقتصادي في الجزائر، ولهذا الغرض تم استخدام نموذج أشعة الانحدار الذاتي (VAR) وبيانات فصلية تغطي المدة من الثلاثي الأخير لسنة 2007 إلى ديسمبر 2019، حيث تم استخدام مؤشرين للشمول المالي ( حجم القروض المحلية و الودائع ) كمتغيرين مستقلين و الناتج المحلي الإجمالي كمتغير تابع يمثل النمو الاقتصادي. ومن نتائج الدراسة المjوصل إليها هو وجود علاقة بين الشمول المالي والنمو الاقتصادي lمن خلال معامل التحديد R²=0.97 والذي يوضح أن المتغيرات المستقلة تفسر المتغير التابع الذي يتمثل في الناتج المحلي الإجمالي PIB بنسبة 97 بالمئة. This study aims to identify the impact of financial inclusion on economic growth in Algeria, in terms of reviewing the concept of financial inclusion, its importance and objectives, and its relationship to economic growth. For the year 2007 to December 2019, where two indicators of financial inclusion (the volume of domestic loans and deposits) were used as independent variables and GDP as a dependent variable representing economic growth. One of the results of the study is the existence of a relationship between financial inclusion and economic growth through the coefficient of determination R² = 0.97, which shows that the independent variables explain the dependent variable represented in the gross domestic product (PIB) by 97 percent.